Surgical treatment of ventricular septal defect combined with tricuspid valve insufficiency - L. Maniuc (Кардіохірургія та інтервенційна кардіологія)
The aim – to evaluate different methods of surgical treatment of ventricular septal defect (VSD), combined with failure of the tricuspid valve (TC), and to develop optimal algorithm for the treatment of patients with this pathology. Materials and methods. Between 2010 and 2014, 35 patients, average age 80.9±20.5 months, underwent tricuspidal annuloplasty within correction of VSD in Center of Cardiac Surgery of Republic of Moldova. Tricuspidal regurgitation of the II grade was diagnosed valve in 20 (57.0 %) cases, III grade – in 8 (23.0 %) cases, IV grade – in 7 (20.0 %) of cases. Within correction of VSD plastics of tricuspidal valve was performed: in 4 cases (11.0 %) of patients plastics by De Vega, in 14 cases (40.0 %) of patients – comissuroplastics, in 6 cases (17.0 %) – comissuroplastics and suture of cleft, in 1 case (4.0 %) plastics by De Vega with comissuroplastics, in 10 cases (29.0 %) – comissuroplastics and suture of cleft. Results. After operation the clinic status improved significantly: breathlessness reduced from 91.7 % to 8.3 % cases, tachycardia reduced from 91.7 % to 33.3 % cases and other cardiac failure symptoms – from 10.8 % to 4.2 % cases. The number of patients with NYHA class I heart failure after surgery was 54.2 % compared to its absence before operation, class 2 diminished from 60.0 % to 41.7 % cases, class 3 – from 36.0 % to 4.2 % cases. Conclusions. Anteroseptal comissuroplastics was used in majority of cases. This method is simple, reliable and inexpensive, requires not more than 5–10 min and significantly reduces tricuspidal valve insufficiency.